Estratégias de gestão de manutenção predial: um estudo de caso em uma empresa do Polo Industrial de Manaus - Souza, Giovana Silva de (Brasil, 2024)
This article analyzed the internal and external factors that influence the implementation of building maintenance management strategies in a company in the Manaus Industrial Complex. The qualitative research used unstructured interviews with company managers, with data analyzed through content analysis. Documentary research was also used to complement the data and enrich the analysis of maintenance challenges and practices. The main findings indicate that the effectiveness of maintenance management is limited by factors such as the production-oriented organizational culture, the dependence on specialized labor and a restricted budget, which directly compromises the sector's delivery capacity and hinders the execution of strategies, affecting equipment availability. The study highlights the importance of a preventive culture and the adoption of emerging technologies, such as the Internet of Things (IoT) and Business Information Modeling (BIM), which can optimize processes and reduce costs in the long term. The research results contribute to the understanding of the dynamics that impact maintenance management in industrial environments, showing that an organizational culture that prioritizes operational efficiency and the use of innovative technologies can significantly improve maintenance management. It is concluded that well-structured management and technological support are essential to increase the efficiency and sustainability of operations, promoting a strategic approach that favors the competitiveness and growth of companies.